Webster's third new international dictionary of the English language with the seven language dictionary. -- Unabridged. (Chicago : Encyclopedia Britannica, 1976)
Contents.--v.1. A to G.--v.2. H to R.--v.3. S to Z.
Keywords: English language -- Dictionaries